Increase mother's knowledge about immunization of measles-rubella with AIMMER mobile phone application - Nur Djanah; Yuliantisari Retnaningsih; Evi Nurhidayati (Jurnal Kesehatan Ibu dan Anak, 2022)
Measles and Rubella are infectious diseases that are easy to spread. Measles is very harmful when accompanied by complications of pneumonia, diarrhea, and meningitis. Rubella may cause a miscarriage and may cause Congenital Rubella Syndrome. The use of the Android smartphone as a product of technological advance has made it possible to develop a system that replaces the role of health professionals. This research is aimed at explaining the influence of immunization application (AIMMER) on parents' knowledge of immunization for children of elementary school age. The design used was a pre-post-test control group. Total sample 136 consists of 68 intervention groups and 68 control groups. The intervention group received education on the application of immunization (AIMMER). The control group received the information from public health centers (PHC) with the SOP implemented. The knowledge level of both groups is measured before and one month after the intervention by using a questionnaire. Analysis using the Mann-Whitney test. There is a significant improvement in the intervention group compared to the control group related to the knowledge level of parents on sequel immunization Measles-Rubella (p=0.001). It can be concluded that the immunization application (AIMMER) can improve the knowledge of parents on sequel immunization of Measles and Rubella.